2006
DOI: 10.1002/ajmg.c.30096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of hematologic and oncologic disorders in patients with Down syndrome

Abstract: Hematologic abnormalities are common in individuals with Down syndrome (DS). Increased erythrocyte mean corpuscular volume (MCV) is frequently found among DS infants and remains elevated throughout life in two-thirds of patients, making interpretation of red cell indices for diagnosis of nutritional anemias or bone marrow failure disorders more challenging. Transient myeloproliferative disorder (TMD) associated with pancytopenia, hepatosplenomegaly, and circulating immature WBCs, is found almost exclusively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 60 publications
2
46
0
4
Order By: Relevance
“…20 Polycythemia is also common in infants with Down syndrome (18%-64%) 21 and may require careful management. Infants with TMD and polycythemia should be followed according to subspecialty consultation recommendations.…”
Section: Evaluate Formentioning
confidence: 99%
“…20 Polycythemia is also common in infants with Down syndrome (18%-64%) 21 and may require careful management. Infants with TMD and polycythemia should be followed according to subspecialty consultation recommendations.…”
Section: Evaluate Formentioning
confidence: 99%
“…4,5 Hematologic abnormalities, such as polycythemia, anemia, thrombocytopenia, thrombocytosis, or increased erythrocyte mean corpuscular volume, are common findings in patients with DS. 6 In addition, 13% to 33% of the patients with TL develop acute myeloid leukemia (AML) within the first 4 years of life. 5,7,8 The unique type of AML in DS is referred to as myeloid leukemia of DS (ML-DS), 8 which is characterized by the frequent occurrence of acute megakaryoblastic leukemia (AMKL or FAB M7-like), a low diagnostic white blood cell (WBC) count, and young age.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Studies have shown that thrombocytopenia and thrombocytosis are not associated with bleeding disorders and thrombosis in DS patients. 10 No hemorrhagic symptoms were present except for present cases diagnosed with acute leukemia and myelofibrosis and present cases with severe thrombocytopenia due to hypersplenism. No cases of thrombosis were observed in present cases.…”
Section: Discussionmentioning
confidence: 57%